Students’ Creative Thinking Abilities and Self Regulated Learning on Project-Based Learning with LMS Moodle - Sudianto, Sudianto; Dwijanto, Dwijanto; Dewi (Nino Adhi), N.R. (Universitas Negeri Semarang, 2019)
The purpose of this study is to examine the effectiveness of project-based learning with LMS Moodle towards the students’ achievement of creative thinking abilities and self regulated learning, and describe how to students’ achievement of creative thinking abilities and self regulated learning. This study uses mixed methods research with concurrent embedded designs. The population in this study were students of senior high school class X at Putra Nirmala Cirebon of 2017/2018 academic year. Data collection techniques used in this study are observation, tests, and interviews. The research subjects were taken based on students’ early mathematical abilities categories, namely above, middle and bottom categories. The findings showed that project-based learning with LMS Moodle was effective to the students’ achievement of creative thinking abilities and self regulated learning. Overall, the students’ achievement of creative thinking abilities and self regulated learning who using project-based learning with LMS Moodle is better than students who using conventional learning. As for contribution (Effect Size) project-based learning with LMS Moodle towards the students’ achievement of creative thinking abilities which are equal to 0.85 while self regulated learning is 0.95. The category of achievement of creative thinking ability and self regulated learning are included in the high category.